Religious Peacebuilding: The Life and Work of Archbishop Raya as a Model for Religious Peacebuilding - Sabada, Lesya Michalina (Université Saint-Paul / Saint Paul University, 2017)
Throughout this dissertation, I argue that the same religion that incites people to hideous acts of violence and destruction can also influence people to act in love, to work toward healing in all stages of conflict, and to offer hope in difficult situations. As Katrien Hertog argues in her major work, The Complex Reality of Religious Peacebuilding, religion has much to contribute to the work of peacebuilding. Unfortunately, as John Paul Lederach and Cynthia Sampson, leading scholars in religious peacebuilding, have pointed out, there are few case studies regarding the peacebuilding activities of religious actors, particularly those who demonstrate a “legitimate connection between spirituality and pragmatic international peacebuilding” (qtd. in Hertog 2010, 40). This dissertation addresses that lack through an examination of the life and work of Joseph Raya, who demonstrated, throughout his life, the importance and effectiveness of a pastoral and prophetic approach (rooted in his Byzantine tradition) in building peace, even in deeply troubled areas of the world. Archbishop Raya can be a model for peacebuilding that is “simultaneously authentic to a religious tradition [Byzantine Christianity] and simultaneously accepting of other traditions” (Gopin 2000, 23). This might be an opportunity for scholarly reflection on one man’s spiritually inspired thought processes that appear to have led to practical pastoral peacebuilding. Thus the research question that shapes this dissertation is “How can the life and teachings of Archbishop Joseph Raya serve as a model for a pastoral and prophetic love-based approach to religious peacebuilding?” My hypothesis is that a practical theology for a pastoral and prophetic approach can be synthesized from Archbishop Raya’s life, actions, and spirituality. The most suitable method of research for this dissertation, with its ultimately practical goal of personal ministry, is qualitative research, specifically a narrative approach appropriate to exploring the life of an individual (Creswell 2004, 78). My organizing principle for this dissertation has been the narrative methodology of Thomas H. Groome which is expressed in five movements. In the first movement, “Naming/Expressing ‘Present Praxis,’” participants name or express their own and/or society’s present action typically around a generative theme (Groome 1998, 146). In this case, the present action is that of Joseph Marie Raya, presented in Chapter 2 as a condensed biography. Although I function here as secondary story-teller, shaping Raya’s action into a chronological coherent whole, that narrative is partially based on Raya’s own writings and oral story-telling, supplemented by primary sources and interviews with those who knew him. The second movement of Groome’s pedagogical method is a “Critical Reflection on Present Action” (Groome 1998, 147) or “The Participants’ Stories and Visions” (Groome 1980, 211). In Chapter 3 of this dissertation, the reflection occurs through my own story of peacebuilding activity, before, during, and after interactions with Archbishop Raya. His continued role as my mentor had a lasting impact on my understanding of Eastern spirituality and religious peacebuilding. It is important for me, in my exploration of what peacebuilding entails in the context of Eastern Catholic Christianity, to examine the effect that Raya’s example has had on me, even before I began to put both stories, Raya’s and mine, into their larger context. The task of the third movement, “The Christian Community Story and Vision” (Groome 1980, 214), is “Making accessible expressions of Christian Story and Vision as appropriate to the generative theme” (Groome 1998, 147). Chapter 4 of the dissertation discusses two contexts of importance for the story of Archbishop Raya: first, the larger context of the emergence of religious peacebuilding as documented by Hertog, and second, the more specific context of the historical development of peace theologies in Roman Catholic, Orthodox, and Melkite Greek Catholic Church traditions. Groome’s fourth movement, the “Dialectical Hermeneutic between the Story and the Participants’ Stories” (Groome 1980, 217), which invites “participants [to] place their critical understanding of present praxis around a generative theme . . . and in dialectical hermeneutics with Christian Story” (Groome 1998, 147), somewhat adapted, is the theoretical base for Chapter 5. Here I revisit the narrative developed in Chapter 2 and critically examine Archbishop Raya as an Eastern Catholic religious peacebuilder through the lens of Hertog’s theory of religious peacebuilding and in the specific situation of the previously identified Churches. That allows me to distill the characteristic elements of Raya’s unique pastoral and prophetic approach to the peacebuilding process and synthesize them into a model for religious peacebuilding. His core principles, based solidly in his Byzantine Catholic Christian tradition and theology, are all undergirded with an overarching love and respect for all people as God’s own beloved children. Out of that love arises 1) a keen awareness of the need for a strong identity and a strong community that are authentic; 2) a consistent emphasis on the need for justice, fueled by compassion for the vulnerable; 3) a strong call for forgiveness and reconciliation; 4) a vigorous effort to educate all people with the purpose of seeking their fullest potential; and 5) a principled commitment to nonviolence. Archbishop Raya is a particularly effective model of these principles because he combined a joyous celebration of life and beauty with unstinting sacrifice; sources show that he did not seek to save his own life or his own dignity or his material possessions or even his hierarchical power. Chapter 5 also looks at inconsistencies and weaknesses in Raya’s life, noting how those weaknesses impacted the effectiveness and the legacy of his peacebuilding ministry. In Groome’s pedagogical context, the fifth movement is a step toward response and change, first through reflecting on personal narratives and their larger contexts and then appropriating what has been learned through suitable actions. Thus Chapter 6 begins with a re-evaluation of my experience of religious peacebuilding, particularly in light of the effect that Archbishop Raya has had on me as a mentor and as an exemplar of principles of peacebuilding. Then I look ahead to the ways in which what I have learned from Archbishop Raya and from the study of the larger stories (the theory of religious peacebuilding and the peace theology of various relevant Churches) can be appropriated in my future peacebuilding endeavours. The final section of Chapter 6 returns to the hypothesis and concludes that the principles of peacebuilding that Archbishop Raya developed through his work and throughout his life can be followed as a guide to pastoral and prophetic religious peacebuilding. Raya can also be an authentic model of such peacebuilding, with two caveats: one is that Raya functioned as an ecclesiastical leader and thus had a degree of authority and influence not available to many lay peacebuilders; the second is that Raya’s approach inherently includes flaws, but can still demonstrate a contribution to the field of religious peacebuilding. The story of Archbishop Raya can be inspirational to religious leaders as well as those with more diverse callings, drawn to serve humanity as peacebuilders based on the foundation of their own particular religious teachings and traditions.
Keywords: Religious Peacebuilding; Eastern Christianity; Melkite Greek Catholic; Ukrainian Catholic; Eastern Christian Theological Resources; Nonviolence; Israel; Labanese Civil War; Martin Luther King Jr.; Trinity; Incarnation; Philanthropia; Archbishop Joseph Raya